Potential Applications of Using 68Ga–Evans Blue PET/CT in the Evaluation of Lymphatic Disorder: Preliminary Observations. (April 2016) - Zhang, Wei; Wu, Peilin; Li, Fang; Tong, Guansheng; Chen, Xiaoyuan; Zhu, Zhaohui
Abstract : Purpose: Potentials of 68 Ga-NEB as a PET tracer in the evaluation of a variety of lymphatic drainage disorders were analyzed. Methods: 68 Ga-NEB was injected subcutaneously, and the PET/CT images were acquired in 13 patients with different suspected lymphatic drainage abnormality. The 68 Ga-NEB PET/CT findings were compared with 99m Tc-SC lymphoscintigraphy. Results: 68 Ga-NEB activity could be clearly observed in the lymphatic route on the PET/CT images from all the patients. In 5 (38.5%) of 13 patients tested, 68 Ga-NEB PET/CT provided more information than the 99m Tc-SC lymphoscintigraphy. Conclusions: 68 Ga-NEB PET/CT can be used as an alternative of 99m Tc-SC lymphoscintigraphy in the evaluation of lymphatic disorders, which enables fast results and might be more accurate than the conventional 99m Tc-SC lymphoscintigraphy.